A novel sandwich graft technique in repair of nasal septal perforation - Essam Abd El Wanes Behery; Ibrahim Ahmed Abd Elshafy; Ahmed Elsayed Elsayed Elesawy; Ashraf Ali Aldemerdash (The Egyptian Journal of Otolaryngology)
Abstract Objective Assess the efficacy of the sandwich graft technique from the concha of auricle or the rest of nasal septum of 2-mm thickness of cartilage with both layers of its perichondrium in the treatment of moderate perforations of the nasal septum (diameter: 1 to 2 cm). Background Nasal septal perforations (NSPs) are bilateral mucosal deformities accompanied by cartilage or defect in the bone. The only permanent solution for NSP is the surgical repair of the defect. Methods Thirteen instances with moderate nasal septal perforations (1 to 2 cm in diameter) which were managed using an endoscope-assisted intranasal approach as well as the sandwich technique from April 2022 to April 2024 were enrolled in the study. Following up lasted for 3 months. Results In 13 instances, the sandwich technique was implemented. Twelve cases were entirely cured (92.3%). A matter is partially closed. Conclusions Fixing moderate nasal septal perforation (1 to 2 cm) with an endoscopic sandwich graft is a straightforward procedure with an elevated probability of achievement.